Increasing Students’ Writing Skill on Poetry through Quantum Learning Strategy: A Classroom Action Research - Darmanah Darmanah (Journal of English Language Teaching and Cultural Studies, 2020)
The purpose of this study is to measure the improvement of the students' writing skills on poetry by implementing quantum learning strategy at tenth-grade of MAN 1 Kota Serang. The research question is stated as follows: (1) can quantum learning strategy improve students’ writing skill on poetry at tenth-grade of MAN I Kota Serang? (2) how it can be implemented to improve students’ writing skills on poetry at tenth-grade of MAN I Kota Serang. The researcher used classroom action research as its method. The pre-activity result shows that the average scores of students writing is 57.44. This result, then, tried to be improved by using quantum learning strategy. Since quantum learning is implemented, the mean of students’ scores in cycle 1 improves 13.38% into 66.32. Since the score is still lower than ideal score, which is 75, the research is continued to cycle 2. The result in cycle 2 shows the improvement of students’ score into 77.74, or improves 14.68% from cycle 1. This result proves that quantum learning strategy can improve students’ writing skill on poetry.